2015
DOI: 10.1021/acsami.5b00846
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Bacterial Cellulose Aerogels’ Web-like Skeleton for Oil/Water Separation

Abstract: The cellulose nanofibers of bacterial cellulose aerogel (BCA) are modified only on their surfaces using a trimethylsilylation reaction with trimethyichlorosilane in liquid phase followed by freeze-drying. The obtained hydrophobic bacterial cellulose aerogels (HBCAs) exhibit low density (≤6.77 mg/cm(3)), high surface area (≥169.1 m(2)/g), and high porosity (≈ 99.6%), which are nearly the same as those of BCA owing to the low degrees of substitution (≤0.132). Because the surface energy of cellulose nanofibers de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
231
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(242 citation statements)
references
References 69 publications
9
231
1
1
Order By: Relevance
“…Such observations indicated that the applied chemical modifications involved essentially hydroxyl groups on the fibers' surface or those in the amorphous regions of WBC, while the internal structure of the fibers was not affected (Tomé et al 2011;Lee et al 2011). A similar phenomenon was reported for surface modification of nanocellulose by organic acids (Ramírez et al 2014) and trimethylchlorosilane (Sai et al 2015), for example.…”
Section: Grafting Of Pnipam Brushes From the Wbc-g-bib Sheetsupporting
confidence: 68%
“…Such observations indicated that the applied chemical modifications involved essentially hydroxyl groups on the fibers' surface or those in the amorphous regions of WBC, while the internal structure of the fibers was not affected (Tomé et al 2011;Lee et al 2011). A similar phenomenon was reported for surface modification of nanocellulose by organic acids (Ramírez et al 2014) and trimethylchlorosilane (Sai et al 2015), for example.…”
Section: Grafting Of Pnipam Brushes From the Wbc-g-bib Sheetsupporting
confidence: 68%
“…[1][2][3] Traditional oil/water separation methods such as flotation, centrifugation or filtration usually involve complicated operations and time-consuming processes. [15][16][17][18][19][20][21][22][23][24][25][26] For example, pioneering work of Jiang group reported using a Teflon coated mesh to separate oil/water mixture. [5][6][7][8][9][10][11][12][13][14] Up to now, various superhydrophobic porous materials have been prepared via various chemical and physical strategies.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Yang et al 39 prepared a novel diisocyanate-modied lignin xerogel using renewable lignin as the precursor via a solgel process and ambient pressure drying method. The asprepared xerogel showed high performance in self-cleaning and superhydrophobicity without further hydrophobic modi-cation.…”
Section: -8mentioning
confidence: 99%